TENSILE, PHYSICAL AND CHEMICAL CHARACTERIZATION OF PAN FIBRE MODIFIED WITH OLEIC ACID POST SPINNING TREATMENT - MD SALLEH, SHAHRUL NIZAM (2017)
Carbon fibre is defined as a fibre with at least 92% carbon in the structure. The fibre has a high tensile property, low density, high thermal and chemical stabilities. Due to its excellent properties, the carbon fibre is used in aerospace, military, turbine blades, construction, pressure vessels, medical, automobile and sporting goods